Sosialisasi Anti Bullying di Pondok Pesantren Al Hamidiyah Sionggoton Desa Janji Matogu Kecamatan Simangambat Kabupaten Padang Lawas Utara - Sahbudi; Yeltriana; Ismed batubara; Ahmad Haris Nasution; Maraiman Siregar (Jurnal Ragam Pengabdian, 2025)
Based on 2024 data from KPAI, reporting of bullying cases in the world of education and social media reached 2,473 reports. The high data on bullying cases shows that bullying cases cannot be underestimated and looked down on by all of us because bullying behavior has a negative impact that can cause a child who receives bullying to become a child who is afraid to express himself. This also happened at the Al Hamidiyah Islamic Boarding School and the main problem in this PKM is the extent to which the students of the Al Hamidiyah Sionggoton Islamic Boarding School, Janji Matogu Village, understand the meaning and impact of  Bullying behavior according to Article 54 of Law 35 of 2014. This activity is expected to help students in the Islamic boarding school (pesantren) in Janji Matogu Village understand the meaning and impact of bullying on students still in school, especially at the Al Hamidiyah Sionggoton Islamic Boarding School in Janji Matogu Village. The method used was a lecture and interactive  session. Twenty-five participants attended, and the results showed an increase in understanding, demonstrated by their enthusiasm for asking questions and their commitment to not repeat bullying by the perpetrators. It is recommended that teachers at the Al Hamidiyah Sionggoton Islamic Boarding School pay more attention to students who engage in bullying, both victims and perpetrators, to prevent bullying from occurring in the school environment. They should also educate each student about the negative impacts of bullying within the school environment.